Researching and Transforming Adult Learning and Communities: The Local/Global Context (Revista Lusófona de Educação, 2017)
Recensão crítica da obra de Rob Evans, Ewa Kurantowicz e Emilio Lucio-Villegas (Edts.) (2016). Researching and Transforming Adult Learning and Communities: The Local/Global Context. Roterdão: Sense Publishers, 197 p.